Wordle : Gamification in Enhancing Students’ Vocabulary - Nurmansyah, Nurmansyah; Suhana, Risky Ratri; Nasrudin, Nasrudin; Hamid, Sitti Maryam (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2024)
This study explores the integration of Wordle, an online word puzzle game, as a learning medium to enhance vocabulary acquisition among eighth-grade students. Gamification and Information and Communication Technology (ICT) plays a crucial role in reshaping educational systems, and Wordle's unique features make it an engaging tool for language learning. The study employs a quasi-experimental design and involved 40 students of a public school in Bulukumba, comparing an experimental class using Wordle with a control class receiving traditional instruction. Statistical analyses, including normality and homogeneity tests, paired sample t-tests, and N-gain score calculations, reveal significant differences in vocabulary acquisition between the two classes. The experimental class, using Wordle, demonstrated a more substantial increase in vocabulary proficiency compared to the control class. The findings suggest that incorporating innovative tools like Wordle can contribute to more effective language education, addressing challenges in vocabulary acquisition and enhancing overall learning outcomes. The study recommends the inclusion of words in English vocabulary teaching, emphasizing the importance of educators adapting to students' learning styles and leveraging technology for improved learning experiences.